Floodplain Surface‐Water Circulation Dynamics: Congaree River, South Carolina, USA - Shailesh van derSteeg; Raymond Torres; Enrica Viparelli; Haiqing Xu; Edwin Elias; Jessica C. Sullivan (Water Resources Research)
Abstract A robustly calibrated and validated hydrodynamic model depicts flow patterns over a topographically complex floodplain with a heterogeneous main channel levee. Simulations highlight floodplain inundation dynamics for two conditions, the passage of sub‐bankfull and overbank flood waves. Sub‐bankfull inundation commences with the passage of the flood wave crest beyond the lower elevation levee breaches, and floodplain wetting is guided by the channel network. Hence, the upstream sub‐bankfull inundation area expands while much of the downstream floodplain remains dry. The onset of overbank flow is spatially variable but becomes continuous, and the through‐bank channels persist as preferential pathways that produce higher velocity flows several kilometers inland. Meanwhile, near‐stagnant zones develop between through‐bank channel mouths, where water is temporarily stored and routed to the channel network. Also, 48% of the inundation water is from the river while 52% enters the study area from the upstream floodplain. Overall, floodplain wetting and draining processes significantly influence flow direction, and characteristics of the flood wave over the floodplain surface such that a single stage in the main channel does not uniquely define floodplain flow hydraulics. Given these findings we propose that assessments of floodplain hydraulic connectivity account for the effects of heterogeneous levee structure and intra‐floodplain exchanges, as well as the typical flow thresholds associated with submergence and emergence of topography.